2020
DOI: 10.3332/ecancer.2020.1067
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and its impact on gynaecologic oncology practice in India—results of a nationwide survey

Abstract: The COVID-19 pandemic sweeping across the world has caused major disruptions in healthcare delivery and practice. A survey was conducted to assess the changes in the care of gynaecologic oncology patients in India. Methods: An online survey enquiring about the patient volumes and surgical load, and changes in practice protocols for endometrial, ovarian, cervical and vulval cancers was conducted in May, 2020. Results: The total number of responses received was 153. Barring duplicates, 148 were analysed. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…According to an online survey in India, it appeared that the volume of patients in cancer centers had reduced, with risk of patients having delayed diagnosis and presenting at more advanced and potentially incurable stages of disease [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to an online survey in India, it appeared that the volume of patients in cancer centers had reduced, with risk of patients having delayed diagnosis and presenting at more advanced and potentially incurable stages of disease [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study, a survey among healthcare professionals in India involved in the care of gynecologic cancer patients, assessed the difference between government and private hospitals. 18 This study identified that government hospitals had higher patient concentration rates than private hospitals before the pandemic. Government hospitals in this study reported higher proportions of practice decrease during the pandemic.…”
Section: Discussionmentioning
confidence: 93%
“…Treatment private hospitals. 18 This study identified that government hospitals had higher patient concentration rates than private hospitals before the pandemic. Government hospitals in this study reported higher proportions of practice decrease during the pandemic.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A survey done on clinicians practising gynaecologic oncology found significant fall in patient volumes, especially in government hospitals after COVID lockdown. 11 In an early analysis reported by Patil et al showed drop in footfalls in a retrospective audit of adult medical head neck cancer unit of apex tertiary cancer hospital. 12 Indian Association of Surgical Oncology mandated routine COVID-19 testing before any surgery.…”
Section: Discussionmentioning
confidence: 99%